CAUSAL FACTORS OF COMPETENCY AN INFLUENCING THE STRATEGY FOR THE POTENTIALITY DEVELOPMENT OF LABOR ON THE AUTOMOTIVE INDUSTRY IN THAILAND - Anan Khieopud, (PEOPLE: International Journal of Social Sciences, 2025)
The objective of research are 1) to study the causal factors affecting the competency and potentiality development of labor on the automotive industry. 2) to study the influencing of competency that affected to the potentiality development of labor on the automotive industry. 3) to create a model of causal factors of competency an influencing the strategy for the potentiality development of labor on the automotive industry. This article is to present knowledge derived from a literature review on Causal Factors of Competency an Influencing the Strategy for the Potentiality Development of Labor on the Automotive Industry in Thailand. The article aims to explain the meaning, background, components, and relationships of variables related to Competency and Strategy for the Potentiality Development of Labor on the Automotive Industry in Thailand. Based on the literature review, the variables commonly used to study Innovative Leadership, Organization Management, Human Resources Management, Competency, Strategy for the Potentiality Development of Labor on the Automotive Industry.